Natriuretic peptide precursor a gene polymorphisms and risk of blood pressure progression and incident hypertension - Conen, David; Glynn, Robert J; Buring, Julie E; Ridker, Paul M; Zee, Robert Y L (Hypertension (Dallas, Tex. 1979), 2007)
We tested the hypothesis that natriuretic peptide precursor A gene polymorphisms are significantly associated with blood pressure progression and incident hypertension among healthy, middle-aged women. We performed a prospective cohort study among 18 437 white women participating in the Women's Health Study who were free of hypertension at baseline. Two previously characterized single nucleotide polymorphisms within the natriuretic peptide precursor A gene (rs5063 G>A and rs5065 T>C) were genotyped. Blood pressure progression at 48 months and incident hypertension during the entire follow-up according to the different genotypes and inferred haplotypes were assessed by logistic regression and Cox proportional hazards models, respectively. At 48 months, 47.4% of women had blood pressure progression. The odds ratio (95% CIs) for blood pressure progression associated with the rs5063 variant was 0.85 (0.76 to 0.94; P=0.002). For the rs5065 variant, the corresponding odds ratio was 0.94 (0.88 to 1.00; P=0.050). During 9.8 years of follow-up, 29.6% of women developed incident hypertension. Hazard ratios (95% CIs) for incident hypertension were 0.88 (0.80 to 0.96; P=0.005) for the rs5063 variant and 0.95 (0.90 to 1.00; P=0.068) for the rs5065 variant. The odds ratios (95% CIs) of blood pressure progression for the G-T, G-C, and A-T haplotypes were 1.0 (referent), 0.91 (0.85 to 0.98; P=0.007), and 0.80 (0.71 to 0.89; P<0.001), respectively. For incident hypertension, the corresponding hazard ratios were 1.0 (referent), 0.95 (0.90 to 1.01; P=0.095), and 0.90 (0.81 to 0.99; P=0.031), respectively. If corroborated by other large-scale, prospective studies, our findings indicate that the natriuretic peptide precursor A gene plays a significant role in blood pressure regulation and development of hypertension.